2020
DOI: 10.3390/nu12061651
|View full text |Cite
|
Sign up to set email alerts
|

A Double-Blind, Randomized Placebo-Controlled Trial of Probiotic Lactobacillus casei Shirota in Stable Cirrhotic Patients

Abstract: Background: In cirrhosis, a pathological gut microbiome has been linked with immune dysfunction. A pilot study of probiotic Lactobacillus casei Shirota (LcS) in alcoholic cirrhosis demonstrated significant improvement in neutrophil function. This study aimed to evaluate the efficacy of LcS on neutrophil function and significant infection rates in patients with cirrhosis. Methods: 92 cirrhotic patients (Child–Pugh score ≤10) were randomized to receive LcS or placebo, three times daily for six months. Primary en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 40 publications
1
31
0
Order By: Relevance
“…Clinical trials also confirm the immunomodulatory properties of lactobacilli in humans. Macnaughtan et al showed that L. casei -treated human patients with cirrhosis had lower plasma MIP-1B concentrations in an 8-week course; IL-1B and MPC-1 –in the alcoholic patient subgroup- and IL-17 –in the non-alcoholic cohort- plasma concentrations were also reduced [ 148 ]. Another clinical study reported that an L. reuteri -antibiotic combined therapy reduced abdominal pain and inflammatory markers (C-reactive protein levels) in acute uncomplicated diverticulitis patients; while also lowering hospitalization time [ 67 ].…”
Section: Anticandidal Properties Of Lactobacillimentioning
confidence: 99%
“…Clinical trials also confirm the immunomodulatory properties of lactobacilli in humans. Macnaughtan et al showed that L. casei -treated human patients with cirrhosis had lower plasma MIP-1B concentrations in an 8-week course; IL-1B and MPC-1 –in the alcoholic patient subgroup- and IL-17 –in the non-alcoholic cohort- plasma concentrations were also reduced [ 148 ]. Another clinical study reported that an L. reuteri -antibiotic combined therapy reduced abdominal pain and inflammatory markers (C-reactive protein levels) in acute uncomplicated diverticulitis patients; while also lowering hospitalization time [ 67 ].…”
Section: Anticandidal Properties Of Lactobacillimentioning
confidence: 99%
“…The SC cohort consisted of patients under follow-up in the outpatient clinic with a clinical, histological, or radiological diagnosis of liver cirrhosis (Child-Pugh score < − 10). 13 The study was approved by the joint University College London (UCL)/UCL Hospitals (UCLH) Committees (http://www.isrctn.com/ ISRCTN62619436), and written informed consent was obtained from each patient included in the study (Fig. 1).…”
Section: Control Cohortsmentioning
confidence: 99%
“…[37][38][39] However, the major drawback of routine antibiotic prophylaxis is the emergence of multidrug-resistant organisms. 34 Thus, novel therapies have been proposed based on their ability to modify the altered intestinal microbiota such as probiotics and prebiotics, 19,[40][41][42][43][44][45] fecal microbiota transplantation, 46,47 phage therapy, 31 among others. Evidence for their use in clinical practice is limited and all require further studies.…”
Section: Intestinal Dysbiosismentioning
confidence: 99%